The 3rd alternative : solving life's most difficult problems - Covey, Stephen R.; England, Breck, 1952- (New York : Free Press, 2011)
Outlines a breakthrough approach to conflict resolution and creative problem solving that draws on the techniques of thinkers from a broad range of disciplines to explain how to incorporate diverse viewpoints for win-win solutions.
Includes bibliographical references and index.
Keywords: Problem solving; Interpersonal conflict; Change (Psychology).